Meninos não choram? um estudo sobre fracasso escolar e jovens masculinidades no ensino médio - Rodriguez, Fernanda Ribeiro Pinto (2009)
The issue of school failure has been much discussed today. Dropout rates and school failure are significant, especially when considering males. Investigate information on school failure, either as repetition or as abandonment, allowed a more sensitive look at this problem in our society and enabled reflection on how much there is to be done in relation to secondary education because, in that it proposes universal primary education, little has been done to ensure the continued education so that students have completed basic education. Thus, based on statistical data and studies that indicated that boys tend to fail in school, believe it would be possible to assume that the meanings attributed by these young avoidance may be related to your becoming a man. Thus the central question of our research was: To what extent the process of constitution of masculinity for young men influence or interfere with academic failure? Were wondering how young males who have left school during the stage of secondary education, signify his or her story (s) of school leavers and to what extent the meanings attributed by these young dropout are related to the process of constitution their masculinities. We adopted the Gender and Youth categories to make research on the failure of young men who escaped and returned to school. The aim of our study was to analyze the relationship between the young men trace constitution of their masculinities and school failure. We used interviews with 12 young males, 7 who had escaped and returned to school and 5 that are evaded. And we conducted a focus group with the group that returned. From the information obtained in the interviews and focus groups, we can infer that the issue of masculinity influence truancy these boys, since it relates, among others with the appearance of independence, responsibility and resistance model adopted by the school current in which it is expected that the subjects are seen only as a student , being forgotten because they are young.